2021
DOI: 10.1371/journal.pntd.0009688
|View full text |Cite
|
Sign up to set email alerts
|

Loss of binding antibodies against rabies in a vaccinated dog population in Flores Island, Indonesia

Abstract: Effective parenteral vaccines are available to control rabies in dogs. While such vaccines are successfully used worldwide, the period between vaccine boosters required to guarantee protection of the population against rabies varies between vaccines and populations. In Flores Island, Indonesia, internationally and locally produced rabies vaccines are used during annual vaccination campaigns of predominantly free-roaming owned domestic dogs. The study objective was to identify the duration of the presence and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…The majority of free-roaming dogs in Indonesia, as in most of developing countries, are aged <1 year and have a poor BCS as a consequence of insufficient nutrition uptake or parasitic diseases ( 16 ). The influence of BCS on the losing antibody titre has been reported in the previous studies ( 17 ). In a prospective study, Wera et al found that the dogs with low BCS tend to more rapidly lose detectable antibody titres after vaccination than dogs with high BCS ( 17 ).…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…The majority of free-roaming dogs in Indonesia, as in most of developing countries, are aged <1 year and have a poor BCS as a consequence of insufficient nutrition uptake or parasitic diseases ( 16 ). The influence of BCS on the losing antibody titre has been reported in the previous studies ( 17 ). In a prospective study, Wera et al found that the dogs with low BCS tend to more rapidly lose detectable antibody titres after vaccination than dogs with high BCS ( 17 ).…”
Section: Introductionsupporting
confidence: 67%
“…The influence of BCS on the losing antibody titre has been reported in the previous studies ( 17 ). In a prospective study, Wera et al found that the dogs with low BCS tend to more rapidly lose detectable antibody titres after vaccination than dogs with high BCS ( 17 ). However, to which extent the dogs develop binding antibodies after vaccination has not yet been analysed in these populations.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations